The optimal WC cut-off points for the prediction of subclinical CVD as measured by carotid intima-media thickness among African adults: a cross-sectional study - M. C. Ringane (BMC, 2021)
Abstract Background Increased waist circumference (WC) is one of the cardiovascular disease (CVD) risk factors used to predict cardiovascular events. Waist circumference cut-off values for predicting metabolic syndrome and other cardiovascular risks have been previously studied. Carotid intima-media thickness (CIMT) is one of the cardiovascular risk factor recently described and reported to be suitable as it is a direct measurement of vascular quality. Hence the aim of the present study was to determine the optimal WC cut-off point for the prediction of subclinical CVD. Methods The study was a cross-sectional study using quantitative methods, conducted among 1318 adults aged between 40 and 60 years old, residing in a rural Black population in Limpopo province. Carotid Intima-Media Thickness measurements were performed using a LOGIQ ultrasound system (GE Healthcare, CT, USA). Waist Circumference (WC) (cm) was measured to the nearest 0.1 cm. Bivariate correlation, logistic regression and receiver operating characteristic were analysed using the statistical package for social sciences version 26.0 software. Results Among the total population, 69% were women and 31% men with a mean age of 53 ± 7 years. Among women, WC at a cut-off value of 95 cm gave the highest sensitivity of 57%, the specificity of 55% and an area under the curve (AUC) of 0.588. In men, an optimum WC cut-off point of 82 cm yielded the highest sensitivity and specificity at 72% and 70% respectively, with an AUC of 0.767 p < 0.001. Conclusion The traditional waist circumference cut-off points (94 cm for women and 80 cm for men) that are currently used for the diagnosis of metabolic syndrome might not be suitable in the prediction of an increased CIMT.